Tài nguyên giáo dục mở - yếu tố tích cực cho đổi mới giáo dục đại học và mục tiêu phát triển bền vững quốc gia - Đỗ, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The shortage of quality learning materials for learning, teaching and research is a major problem affecting the quality of education and research at universities in Vietnam. Open Educational Resources (OER) is considered a feasible solution to this problem. OER enable universities to improve the quality of human resource training as well as their self-reliant capacity and sustainable development. The objective of this study is to identify the current status and role of OER at universities, thereby to recommend the development orientation of OER for higher education in Vietnam. In order to achieve this goal, the study answers the following questions: What are "Open Educational Resources" and why are they important for higher education reform in Vietnam? How are OER being developed in Vietnam? What are the challenges and opportunities (influential factors) in the development of OER?. Then, based on a survey of 40 universities and technology companies, the study team recommends developing OER at national scale in order to build high quality educational resources for students, lecturers and researchers at universities in Vietnam.